A comparative study on prophylactic antibiotic between its short term use and traditional long term use in elective surgery - study of 100 cases - Al Mamun, A; Mustafa, ASMF; Hasan, M; Alauddin, M; Rahman, A; Haque, AHMA (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13240 J. Dhaka Med. Coll. 2012; 21(1): 60-65